SISTEM PENDUKUNG KEPUTUSAN PRIORITAS REHABILITASI BANGUNAN SDN/MIN DI KABUPATEN PULANG PISAU - Micky Prasetia (Lambung Mangkurat University Press, 2019)
The central issue in improving the quality of Indonesia's human resources is improving the quality of basic education. One aspect that affects the quality of basic education is the quality of its infrastructure, namely the SDN / MIN buildings. Most of the SDN / MIN buildings in Pulang Pisau Regency are old buildings with an appalling condition. To restore the function of buildings that have been damaged and declined, the Pulang Pisau Education Office carries out physical rehabilitation of buildings deemed necessary to repair. In reality, often, the decision to rehabilitate SDN / MIN buildings is not appropriate as needed. The discrepancy between the decisions of the Regional Government and the existing needs requires a solution in the form of a Decision Support System (SPK) for the rehabilitation of SDN / MIN buildings as a reference in making decisions. The study was conducted by taking a sample of one school for one district. Primary data obtained from the distribution of questionnaires by purposive sampling and secondary data obtained from the Central Statistics Agency. Making SPK begins with the collection of school damage data. Data on building damage is entered into a database. The database is created with a computer application. Damage data is determined by weight. Analytical Hierarchy Process (AHP) method is used as a scientific way to determine the priority order of rehabilitation of SDN / MIN buildings. SPK is made based on computer applications, so it is fast and easy to use in making decisions. Computer-based SPK has been validated and compared with manual calculations, and the conclusion is no different. SPK application system created has been verified and proven to be easy to operate.